A new record of Tricholoma caligatum (Tricholomataceae) from North Africa with a discussion of related species - (:unkn) unknown (My University, 2016)
Among the Basidiomycota, matsutake are the most appreciated mushrooms in Japan. Some Tricholoma species belonging to matsutake group are exported from North Africa to Japan. Until the beginning of the 21st century, the North African ‘matsutake’ was identified as T. caligatum, which is a circum-Mediterranean species described in 1834. However, recent molecular analyses uncover some North African isolates as T. anatolicum, which is a species described from Turkey in 2003. As a result, the presence of T. caligatum in North Africa remained to be confirmed. We analyzed a recent specimen collected in Algeria from mixed forest and based on molecular and morphological data, we found that it belongs to T. caligatum, indicating the existence of two species in North Africa. Morphological traits and molecular markers are proposed here to easily distinguish these two species from each other. The concept of both the species and their respective geographic distributions are discussed.
Keywords: African Research